Quantitative assessment of the degree of lipid unsaturation in intact Mortierella by Raman microspectroscopy - Muenchberg, Ute; Wagner, Lysett; Rohrer, Carsten; Voigt, Kerstin; Roesch, Petra; Jahreis, Gerhard; Popp, Jürgen (Analytical and Bioanalytical Chemistry, 2015)
Fungi of the genus Mortierella can accumulate large amounts of unusual lipids depending on species, strain, and growth conditions. Fast and easy determination of key parameters of lipid quality for these samples is required. In this contribution, we apply Raman microspectroscopy to determine the degree of unsaturation for fungal lipids directly inside intact hyphae without elaborate sample handling. Six Mortierella species were grown under varying conditions, and Raman spectra of single lipid vesicles were acquired. From the spectra, we calculate a peak intensity ratio I(1270 cm−1)/I(1445 cm−1) from the signals of =CH and –CH2/–CH3 groups, respectively. This ratio is linked to the iodine value (IV) using spectra of reference compounds with known IV. IVs of fungal samples are compared to gas chromatography results. Values from both methods are in good accordance. Lipid composition is found to vary between the investigated species, with Mortierella alpina having the most unsaturated lipid (IV up to 280) and Mortierella exigua the least unsaturated (IV as low as 70). We find Raman microspectroscopy a suitable tool to determine the IV reliably, fast, and easily inside intact hyphae without extensive sample handling or treatment. The method can also be transferred to other microscopic samples.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Arachidonic acid production; Lipid bodies; Mortierellales; Mortierellomycotina; Oleaginous fungi; Polyunsaturated fatty acids